DECODING DIALOGUE: ANALYZING SUBTITLING STRATEGIES FOR INTERROGATIVE SENTENCES IN THE LUCA MOVIE - Sausani, Celeste; Budiwaty, Suci (UG Journal, 2024)
In the context of contemporary media consumption facilitated by advanced technologies, subtitling serves as a crucial tool for overcoming language barriers in movie viewing. This research delves into the analysis of interrogative sentences and their corresponding subtitling strategies in the Luca movie, an American animated fantasy film. Utilizing Frank's theory for interrogative sentence classification and Gottlieb's theory for subtitling strategies, the study explores communication nuances within the movie's dialogues. Employing a descriptive qualitative method, data was gathered from English-Indonesian subtitles, focusing on interrogative sentences and their subtitling approaches. The findings reveal prevalent types of interrogative sentences, notably Yes-No Questions, and highlight Paraphrase as the dominant subtitling strategy. This study underscores the significance of subtitling in enhancing audience comprehension and facilitating cross-cultural cinematic experiences.